Mast cells and basophils are essential for allergies: mechanisms of allergic inflammation and a proposed procedure for diagnosis - He Shao-heng; Zhang Hui-yun; Zeng Xiao-ning; Chen Dong; Yang Ping-chang (Acta Pharmacologica Sinica, 2016)
The current definition of allergy is a group of IgE-mediated diseases. However, a large portion of patients with clinical manifestations of allergies do not exhibit elevated serum levels of IgE (sIgEs). In this article, three key factors, ie soluble allergens, sIgEs and mast cells or basophils, representing the causative factors, messengers and primary effector cells in allergic inflammation, respectively, were discussed. Based on current knowledge on allergic diseases, we propose that allergic diseases are a group of diseases mediated through activated mast cells and/or basophils in sensitive individuals, and allergic diseases include four subgroups: (1) IgE dependent; (2) other immunoglobulin dependent; (3) non-immunoglobulin mediated; (4) mixture of the first three subgroups. According to our proposed definition, pseudo-allergic-reactions, in which mast cell or basophil activation is not mediated via IgE, or to a lesser extent via IgG or IgM, should be non-IgE-mediated allergic diseases. Specific allergen challenge tests (SACTs) are gold standard tests for diagnosing allergies in vivo, but risky. The identification of surface membrane activation markers of mast cells and basophils (CD203c, CCR3, CD63, etc) has led to development of the basophil activation test (BAT), an in vitro specific allergen challenge test (SACT). Based on currently available laboratory allergy tests, we here propose a laboratory examination procedure for allergy.